Effect of hydrogenated iron oxide nanoparticles with regular spherical shape by underwater plasma discharge treatment for high-efficiency water purification. Issue 15 (15th October 2020) - Jeong, Yesul; Park, Ji-In; Ha, Myoung Gyu; Bae, Jong-Seong; Choi, Yunju; Choi, Sun-A; Oh, You-Kwan; An, Ha-Rim; Kim, Hyeran; Kim, Hae Jin; Lee, Sang Moon; Lee, Suok; et al.
Abstract: We have developed a template-free, easily controllable, and simple method for the mass production of hydrogenated iron oxide nanoparticles (NPs). These NPs were formed with a regular spherical shape by underwater plasma discharge treatment at room temperature and atmospheric pressure. The various phases of well-crystallized iron oxide NPs were carefully monitored by controlling the amount of hydrazine. Further, the obtained Brunauer–Emmett–Teller surface area of 67.86 m 2 /g was much larger than that of a commercial sample (32.40 m 2 /g), which was further increased to 85.07 m 2 /g by adjusting the amount of hydrazine. The removal efficiency for heavy metal and organic dyes was obtained to be 100%, which was 10 times faster than that of the commercial sample. Furthermore, 100% flocculation efficiency was obtained by using only 6 g/g microalgal cell of the prepared iron oxide, whereas no significant change was observed for commercial iron oxide irrespective of the amount of flocculant. These excellent efficiencies for the removal of pollutant from waste water can be originated in the high specific surface area, relatively positively charged surface, and good crystallinity of the synthesized samples. These indicate that the hydrogenated iron oxide NPs in this study are potentially useful for water purification by serving as an adsorbent, photocatalytic material, and flocculant.